Chromatin regulatory dynamics of early human small intestinal development using a directed differentiation model. Issue 2 (6th January 2021) - Hung, Yu-Han; Huang, Sha; Dame, Michael K; Yu, Qianhui; Yu, Qing C; Zeng, Yi A; Camp, J Gray; Spence, Jason R; Sethupathy, Praveen
Abstract: The establishment of the small intestinal (SI) lineage during human embryogenesis ensures functional integrity of the intestine after birth. The chromatin dynamics that drive SI lineage formation and regional patterning in humans are essentially unknown. To fill this knowledge void, we apply a cutting-edge genomic technology to a state-of-the-art human model of early SI development. Specifically, we leverage chromatin run-on sequencing (ChRO-seq) to define the landscape of active promoters, enhancers and gene bodies across distinct stages of directed differentiation of human pluripotent stem cells into SI spheroids with regional specification. Through comprehensive ChRO-seq analysis we identify candidate stage-specific chromatin activity states, novel markers and enhancer hotspots during the directed differentiation. Moreover, we propose a detailed transcriptional network associated with SI lineage formation or regional patterning. Our ChRO-seq analyses uncover a previously undescribed pattern of enhancer activity and transcription at HOX gene loci underlying SI regional patterning. We also validated this unique HOX dynamics by the analysis of single cell RNA-seq data from human fetal SI. Overall, the results lead to a new proposed working model for the regulatory underpinnings of human SI development, thereby adding a novel dimension to the literature that has relied almost exclusively on non-human models.